Sabang Free Port 1962-1985, Indonesia - Malik, Maryana; Suprayitno, Suprayitno; Ratna, Ratna (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
The port was initially only an exile area that turned into a port reckoned in Aceh. In addition, Sabang Port was one of the transito ports that survived only during the Colonial period of the Netherlands. Sabang Port in the time of independence was functionalized as an import-export port. The review uses historical methods in its research process. On the source collection process, sources are used in the form of colonial archives, reports, books, thesis and field studies in the form of interviews on the activities of portage in the Port of the Sabang. The review aims to explain the existence and activity of the Port of Sabang. To support such purposes it was also described the general conditions of Sabang Port during colonial times and Sabang Port conditions in the time of independence.